First report of Athelia rolfsii (=Sclerotium rolfsii) causing foot rot disease of chia (Salvia hispanica L.) in India - Joy, Josna; Mahadevakumar, S; Mamatha Bhanu, L S; Niranjan Raj, S; Chandranayaka, S; Lakshmidevi, N (Plant disease, 2022)
Salvia hispanica L. (Lamiaceae) commonly called 'chia' is an important food crop that has gained significance in recent times globally due to its nutritive value. During a field survey (Mysore district, Karnataka, October, 2021), chia fields were found associated with a characteristic foot rot disease. Further, the presence of mycelial structures along with sclerotial bodies was recorded near the stem-soil interface on the infected plants. The disease incidence ranged 15-21% in an area of approximately 15 hectares of chia fields. The symptoms initially appeared as tan lesions near the stem soil interface and the lesions were colonized by the fast growing mycelium. As the disease progressed, the plants toppled due to death of the stem-root interface region. Infected plants from KM Halli (12º20'90"N; 76º37'68"E) and DMG Halli (12º28'50"N; 76º51'66"E) (n=30) were sampled and associated fungal pathogen isolated on potato dextrose agar (PDA; HiMedia Lab, Mumbai). Fungal mycelia developing from the infected tissues were inoculated on to fresh PDA plates to obtained pure cultures for further identification. Fungal colonies with dense, aerial whitish-cottony mycelia with uniformly globoid sclerotia (0.52.9 mm) were observed after 1012 days of incubation at room temperature. Sclerotia were white at first and turned brown with age. The average number of sclerotia produced per plate ranged from 150 to >280 (n = 10). To further to confirm the identity of the isolates, three representative isolates (SrSh1, SrSh5 and SrSh10) was subjected to molecular identification based on ITS-rDNA sequences. Briefly, genomic DNA was isolated from 12 day old cultures using the CTAB method and ITS-rDNA was amplified using ITS1-ITS4 primers (White et al., 1990). An expected amplicon of >650 bp was obtained and later sequenced from both the directions. The consensus sequences were analysed through nBLAST search which revealed that 100% (643/643 bp) sequence similarity with reference sequences of Athelia rolfsii (S. rolfsii) from GenBank database (KY640622 and AB075298). A phylogenetic tree obtained by the neighbor-joining method using MEGAX shared a common clade with the reference sequences retrieved and computed, thus confirming the identification based on sequence analysis and molecular phylogeny. The representative sequence of A. rolfsii isolates SrSh1, SrSh4 and SrSh7 isolates deposited in GenBank with Accession no OM021878-OM021880. Based on etiology, morphological, cultural and molecular data the pathogen was identified as Athelia rolfsii (Curzi) Tu & Kimbrough (Syn: Sclerotium rolfsii Sacc.) (Mordue, 1974; Mahadevakumar et al., 2016, 2018). Pathogenicity tests were conducted by inoculating the sclerotial bodies near stem soil interface of chia plants grown under green house (at 28 ± 2°C and 70% relative humidity). Briefly, a total of 60 healthy plants were inoculated with sclerotia and covered with polythene bags for 2 days and removed later. Plants (n=20) inoculated without any sclerotia were treated as controls. The development of characteristic foot rot disease was observed after 6-8 days post inoculation. A total of 38 plants showed the foot rot symptoms while control plants remained healthy. The identity of the fungus was confirmed by morphology and molecular sequence analysis after re-isolation. Chia is an important food crop and in recent times has been regarded as super food. Although S. rolfsii is known to be associated with many crops, this is the first report in chia. Therefore, to the best of our knowledge, this is the first report of foot rot disease caused by Sclerotium rolfsii on chia in India. Early diagnosis of this disease will help the farmers to adopt suitable management practices to avoid loss.